STIMULATION AND MOTIVATION OF EMPLOYEES IN THE CONTEXT OF INNOVATIVE DEVELOPMENT OF MANAGEMENT SYSTEMS (Development Service Industry Management, 2023)
The article examines the theoretical foundations of motivation and stimulation. The history of formation and development of the main concepts of motivation is characterized. The evolution of the understanding of the basic concepts of employee motivation and the determination of the features of the motivational process in various spheres of innovative activity at enterprises is presented. Theories of motivation are divided into primary and content. Primary ones assume that a person is driven to work by certain needs, motives in the process of activity, which have developed at a certain historical stage. These theories include the "whip and gingerbread" theory, theories "X", "Y", "Z". Meaningful - analyze the factors affecting motivation. To a large extent, the main focus of these theories is focused on the analysis of needs and their impact on motivation. These theories describe the structure of needs, their content, and how needs are related to a person's motivation to act. In these theories, an attempt is made to answer the question of what motivates a person to act. Meaningful theories of motivation are based on the identification of motives that force a person to act in one way or another.The approaches of domestic and foreign scientists to the vision of motivational processes, processes of staff stimulation and determination of needs were studied. Scientific and methodical approaches to understanding the theories "X", "Y", "Z" and the characteristics of meaningful theories of motivation are given. It has been proven that the motivation of innovative development is the stimulation of managerial activity, which is based on the adoption and implementation of progressive decisions with the aim of introducing innovations, and is aimed at achieving personal and innovative goals of the organization's development. A scheme of the motivational process of innovative activity has been developed.
Keywords: motivation; stimulation; innovative development; personnel; management